The Concept of Holistic Hygiene In Islam: The Integration of Taharah And Nazafah - Yono, Yono; Muslimin, JM.; Rusydi, Ibnu (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The concept of cleanliness in Islam covers physical and spiritual aspects, with the integration of taharah (purity) and nazafah (cleanliness). This article explores the holistic hygiene approach in Islamic teachings, emphasizing the importance of maintaining overall cleanliness in everyday life. This study aims to analyze and formulate the concept of holistic hygiene in Islam. This study uses empirical normative legal research methods. Secondary sources used are the Qur'an, hadith books (al-kutub al-tis'ah), fiqh books written by scholars whose credibility is recognized, such as the Hashiyah book I'anat al- Talibin 'ala Hill Alfaz Fath al- Mu'in by Abu Bakr Ibn Muhammad Shata al-Dimyati, al-Tawjih al -Tashri'i al-Islamiy fi Nazafat al-Biah wa Sihhatiha by Abdullah Qasim al-Washli, Ri'ayat al-Biah fi Shari' at al-Islam by Yusuf al-Qardawi and Fiqh al-Bi'ah fil Islam by Mustafa Abu Sway. Data collection techniques are carried out by literature review. The findings of this study indicate that the integration of taharah and nazafah has a holistic hygiene concept in Islam includes cleanliness of faith, personal and environmental cleanliness and moral-spiritual cleanliness. Regarding environmental cleanliness, the paradigm that must be used is the anthroposophic paradigm by adhering to the 4 K principles, namely the principle of safety, the principle of cleanliness, the principle of purity and the principle of beauty. This study confirms that cleanliness carried out according to Islamic teachings directly impacts the community's physical health.